A mass cyanide poisoning from pickling bamboo shoots - Pensiriwan Sang-A-Gad (2018)
Context. Bamboo shoots contain cyanogenic glycosides named taxiphyllin. Cyanide poisoning from cyanogenic glycosides commonly occurs following ingestion. However, toxicity caused by inhalation of hydrogen cyanide gas (HCN) produced from pickled shoots has never been reported. Objective. To describe cyanide poisoning in eight victims who were exposed to HCN produced in a well containing pickling bamboo shoots. Materials and methods. Due to a series of botched rescue attempts, a total of eight patients entered into a 27 m 3 well containing pickled bamboo shoots and immediately lost consciousness. After rescue, two patients developed cardiac arrest, metabolic acidosis and died. Four other patients suffered metabolic acidosis, but recovered after supportive care. The remaining two regained consciousness and recovered soon after the event. Ambient air study and cyanide content of bamboo shoots helped confirm the diagnosis. Results. All patients had high anion gap metabolic acidosis with normal oxygenation. Blood cyanide levels ranged from 2.66 to 3.30 mcg/ml (taken after about 18 h of incident). Ambient air study (21 h after incident) revealed oxygen 20.9%, and sulfur dioxide 19.4 ppm. The instrument was unfortunately not equipped to detect HCN. A simulation study revealed HCN and sulfur dioxide in the ambient air at 10 ppm and 7.5 ppm, respectively. Cyanide content in the bamboo shoots ranged from 39 to 434 mg/kg in the wet shoots. Discussion. This series of patients developed sudden onset of alteration of consciousness and metabolic acidosis upon exposure, and cyanide was confirmed in all victims. The simulation study confirmed the presence of HCN in the ambient air of the well containing bamboo shoots. Conclusion. We have reported mass acute cyanide poisoning with two fatalities. The source of HCN was unusual as it was produced from pickling bamboo shoot. © 2011 Informa Healthcare USA, Inc.